Prevalence of Interventions After Difficult Airway Response Team Activation: A Systematic Review and Meta-Analysis - Tran, Quincy K; Chen, Chih-Hsuan; Palmer, Jamie; Moran, Madison; Bzhilyanskaya, Vera; Yamane, David; Pourmand, Ali (Respiratory care, 2025)
We sought to define the prevalence of interventions by the Difficult Airway Response Team (DART) following its activation and investigate variables associated with increased risk of surgical airway and successful first intubation attempt. We conducted a systematic review and included 14 studies in our meta-analysis. DART activations in ICUs, general wards, and emergency departments (EDs) were inspected. Variables collected included age, body mass index, and the percentage of subjects with a known difficult airway. Additional data included the DART activation location and time, the method of airway securement, and the number of first successful intubation attempts. The primary outcome was the prevalence of interventions by DART, defined as the number of subjects who underwent intubation by any method or received a surgical airway following consultation and evaluation by the DART. We used random-effects models. Moderator analyses and meta-regressions were performed to identify sources of heterogeneity and clinical variables associated with the prevalence of interventions by DART after its activation, respectively. We included 4,092 subjects with a mean age of 57 (±3) years. Eleven studies reported 36% (1,030) female subjects. There were 3,441 DART activations among subjects in the ED, ICU, and ward. The pooled prevalence of the interventions by the DART, after activation was 76% (95% CI 0.41-0.93). The pooled prevalences of surgical airway placement and first successful intubation attempt was 6% (95% CI 0.03-0.10), and 72% (95% CI 0.61-0.81), respectively. Higher percentage of subjects undergoing video laryngoscopy (VL) was negatively correlated with higher percentage of surgical airway (coefficient -2.7, 95% CI -3.9 to -1.5) and positively correlated with first successful intubation attempts (coefficient 1.6, 95% CI 1.1-2.2). The prevalence of interventions by DART after its activation was high, combined with lower prevalence of surgical airway demonstrate the benefits and efficacy of this emergent difficult airway program. Higher prevalence of successful first attempt was correlated with the usage of VL. Further research endeavors should investigate the efficiency of DART pathways in different institutions.